Germinación y establecimiento de plantas nativas del matorral tamaulipeco y una especie introducida en un gradiente de elevación - García Pérez, Jaime F.; Calderón, Óscar Aguirre; Estrada Castillón, Eduardo; Flores Rivas, Joel; Jiménez Pérez, Javier; Jurado Ybarra, Enrique (Instituto de Ecología, A.C., 2016)
Germination and growth of four plant species were evaluated from 90 to 1960 m above sea level, with the aim to determine whether global warming could influence growth at higher elevations in northeastern Mexico. Three native species (Cordia boissieri, Ebenopsis ebano and Caesalpinia mexicana) and a naturalized species (Melia azederach) were tested. Seeds were set to germinate in containers four times (Spring 2003, 2004, Autumn 2003 and 2004) at five elevations (90, 350, 520, 1600 and 1960  m above sea level). The lowest three elevations encompass the current distribution range of the species, and it was in these elevations that in general germination percentage was higher across species. The highest germination for C. boissieri occurred at 350, 520 and 1600 m above sea level. Highest germination for E. ebano and C. mexicana occurred at 90, 350, 520 and 1600 m above sea level. The highest germination for M. azederach occurred at 90, 350 and 520 m above sea level. In addition, seedling growth and number of leaves produced by seedlings were, in general higher at elevations with highest germination percentages. Results presented here suggest that plant species studied have the capacity to germinate and grow at higher elevations from their current distribution.